PEMBELAJARAN KOOPERATIF JIGSAW UNTUK MENINGKATKAN AKTIVITAS BELAJAR ALQUR'AN - Hidajah, Rochmah (EDUTECH, 2019)
The purpose of this study is to improve the learning outcomes of Islamic Qur'an material PAI, namely student learning activities so that the learning process of Islamic Education runs effec-tively, efficiently, pleasantly and meaningfully. As for the method used is Class Action Research through observation using 3 cycles. Having a change in attitude and behavior in a good direction, being creative, and being responsible is the aim of the education. Al-Qur'an as part of the material on Islamic Education, students should be enthu-siastic in learning, because the Qur'an as a way of life for Muslims. But through preliminary research the results achieved have not been as expected. Students are silent, the learning process is still dominated by teachers, speaking activities are lacking, students do not dare to ex-press opinions or ask questions. Professional teachers must be able to overcome these problems. Many learning models can be chosen to improve student activity, creativity and responsibility. The alternative learning method that makes active students is Jig-saw cooperative learning. The results showed that the level of student learning activities increased by 44.4%. This is indicated by 32.5% in the first cycle to 76.9% in the second cycle and 90.5% in the third cy-cle. Data on student cognitive aspects of learning outcomes also showed increasing results. This result is based on the average value of 78.2 in the first cycle to 84.74 in the second cycle and 86.25 in the third cycle. Student learning activities increased after the implementa-tion of the Jigsaw learning model. This is evidenced by 83.5% of stu-dents who stated yes, 6.75% of students who stated no, 9.75% of stu-dents answered doubtfully. The conclusion of the research results is that the application of the Jigsaw cooperative learning model is very effective, can improve student activities and learning outcomes in Al-Qur'an material.Memiliki perubahan sikap dan perilaku ke arah yang baik, bersikap kreatif, dan bertanggungjawab adalah tujuan pedidikan. Guru berperan untuk keberhasilan sebuah pendidikan. Al Qur`an sebagai  bagian dari materi Pendidikan Agama Islam, seharusnya siswa bersemangat dalam belajar, karena Al Qur`an sebagai pedoman hidup umat Islam. Tetapi melaui penelitian awal hasil yang di capai belum sesuai yang diharapkan. Siswa banyak diam, proses pembelajaran  masih di dominasi oleh guru, aktivitas berbicara kurang,  siswa tidak berani mengemukakan pendapat maupun bertanya. Guru yang profesional harus mampu mengatasi permasalahan tersebut. Banyak model pembelajaran yang dapat dipilih untuk meningkatkan aktifitas, kreativitas maupun tanggungjawab siswa. Alternatif metode pembelajaran yang membuat siswa aktif adalah pembelajaran kooperatif Jigsaw. Hasil penelitian menunjukkan bahwa tingkat aktivitas belajar siswa meningkat 44,4%. Hal ini ditunjukkan dengan 32,5% pada siklus I menjadi 76,9% pada siklus II dan 90,5 % pada siklus III. Data hasil belajar aspek kognitif siswa juga menunjukkan hasil yang meningkat. Hasil ini didasarkan pada rata-rata nilai 78,2 pada siklus I menjadi 84,74 pada siklus II dan 86,25 pada siklus III. Aktivitas belajar siswa menjadi meningkat setelah adanya penerapan model pembelajaran Jigsaw. Hal ini terbukti dengan sebanyak 83,5% siswa yang menyatakan ya, 6,75 % siswa yang menyatakan tidak, 9,75% siswa menjawab ragu. Kesimpulan hasil penelitian adalah penerapan model pembelajaran kooperatif Jigsaw sangat efektif,  dapat meningkatkan aktivitas dan hasil belajar siswa pada  materi Al Qur`an.